LITERARY CRITICISM IN THE DIGITAL AGE: ADDRESSING THE PROBLEMS AND OPPORTUNITIES OF DIGITAL LITERATURE IN EFL PEDAGOGY - Ali Mustofa; Lies Amin Lestari (University of Kuningan, 2023)
The literary genre known as